Mikrostruktur Arang Aktif Batok Kelapa untuk Pemurnian Minyak Goreng Habis Pakai - Rinto Paputungan; Siti Nikmatin; Akhiruddin Maddu; Gustan Pari (Jurnal Keteknikan Pertanian, 2018)
AbstractThe obejective of this study was to investigate the effect of active carbon derived from coconut shell as adsorbents for consumables cooking oil. Method used in this rescarch was started with coconut shell preparation in form of chips and then carbonized and activated as well as morphological analysis by means of SEM. Variation used were activation times of activated carbon of coconut shell for 80, 100 and 120 min. The analysis results showed that the coconut shell charcoal yield was 41.66%, water contents was 3.7767%, ash contents was 2.9997% and Iod adsorbsion was 1051.07 mg/g. Consumables cooking oil refining process by activated charcoal from coconut shells can increased the quality of the oil market by a decrease in water contents, free fatty acids, peroxide value and turbudity numbers. Purification of cooking oil waste with activated carbon as adsorbent was archieved at temperature of 1000C, a contact time of 20 minutes, water contents of 0.10567%, free fatty acids of 0.7933%, peroxide numbers of 21.4667% andturbidity value of 69.7700 NTU.AbstrakPenelitian bertujuan untuk mengetahui pengaruh arang aktif batok kelapa sebagai adsorben pada pemurnian minyak goreng habis pakai. Metode penelitian diawali dengan preparasi batok kelapa dalam bentuk cip, kemudian karbonisasi dan aktivasi, serta pengujian morfologi arang aktif menggunakan SEM. Variasi yang dilakukan ialah lama aktivasi arang aktif batok kelapa 80, 100 dan 120 menit. Hasil yang terbaik analisis arang aktif batok kelapa menunjukkan rendemen 41.66%, kadar air 3.7767%, kadar abu 2.9997% dan daya serap Iodin 1051.07 mg/g. Proses pemurnian minyak goreng habis pakai oleh arang aktif dari batok kelapa dapat meningkatkan kualitas minyak yang ditandai dengan penurunan kadar air, bilangan asam lemak bebas, bilangan peroksida dan angka kekeruhan. Pemurnian limbah minyak goreng dengan adsorben arang aktif batok kelapa, tercapai pada temperatur 1000C, waktu kontak 20 menit, kadar air dalam minyak 0.10567%, bilangan asam lemak bebas 0.7933%, bilangan peroksida 21.4667% dan nilai kekeruhan 69.7700 NTU.